Sinergi Politik Harapan: Interseksionalitas Politik Pemuda dalam Feminisme - Usep Sadikin (Jurnal Perempuan, 2023)
Indonesian youth experience age discrimination (ageism) according to the Domination Matrix in the form of legal structural dominance and cultural hegemony. Law Number 40 of 2009 on Youth defines youth as citizens aged 16–30 years, but a number of political positions in Law Number 7 of 2017 on Elections and Law Number 10 of 2016 on Local Elections have conditions that prohibit youth ages. All youths are prohibited from becoming president/deputy which is implied by the existence of a minimum age requirement of 40 years, governor/deputy (30), and members of the General Election Commission/Election Supervisory Body at central (40), provincial (35) and district/city levels (30). Culturally, the ageism which judges youth to be incapable of leading is natural with the fact that youth have never nominated a youth minister and chairman of National Committee of Indonesian Youth (KNPI). It is important for young people to study the politics of hope for feminism, which in history succeeded in removing the ban on women’s suffrage and succeeded in obtaining political affirmation of at least 30 percent. As a significant number of citizens, the intersectionality of youth in feminism can be a synergy to achieve a more representative parliament, by recognizing one another’s identities within the framework of political expectations.